Costs, viability and risks of organic tomato production in a protected environment - Machado Neto, Andrezza; Ponciano, Niraldo; Souza, Paulo; Gravina, Geraldo; Daher, Rogério (Revista Ciência Agronômica, 2018)
The aim of this research was to evaluate the agro-economic performance of two table-tomato cultivars (Santa Clara and Siluet), under organic cultivation and in a protected environment. Through the analysis of production costs, economic viability and project risk, it was sought to generate a proposal for agricultural profitability having less socio-environmental impact on family farming. To achieve that, the Operating and Total Production Costs, Net Present Value (NPV) and Internal Rate of Return (IRR) were calculated. A sensitivity analysis and economic risk analysis were then carried out. Both cultivars under consideration presented satisfactory economic indicators for the period being analysed. Judging by the criterion of Net Present Value, almost all discount rates (except for the rates of 10 and 12% for the Santa Clara cultivar) were found to be economically viable, with internal rates of return higher than the annual rate of 6%, the minimum rate of financial attractiveness considered. The sensitivity analysis revealed that price received and productivity have the greatest interference on project profitability, followed by packaging and labour costs. The estimated economic risk was relatively low, with a probability of obtaining a negative NPV of 30.31% in the case of the ‘Santa Clara’, and 4.48% for the ‘Siluet’. It is therefore concluded that the organic production of ‘Siluet’ and ‘Santa Clara’ tomatoes under protected cultivation is an economically viable activity, with emphasis on the agro-economic superiority of the Siluet cultivar.